Exploring the application and integration of UAV technology in delivery systems - Gävert, Aleksander (My University, 2024)
The bachelor’s thesis ‘Exploring the application and integration of UAV technology in delivery systems’ discusses the world of autonomous UAV aircraft and how to integrate such technology into delivery systems. The research begins by explaining thoroughly how different airframes operate and their strengths and weaknesses. By proposing a dock that combines both FMS (Flexible Manufacturing Systems) technology and automatization, drones become a viable and useful alternative to car-based delivery systems. Drone based delivery systems have a smaller carbon footprint per delivery kilometre, are faster, and more flexible when comparing fossil fuel hungry car delivery methods. Using an inductive structuring, the thesis discusses aerodynamics, sensor requirements, and hypothetical delivery system based in the city of Turku Finland. In this study the thesis deducts which sectors would benefit from such delivery systems by interviewing personnel from those sectors. The analysis extends to considerations of infrastructure requirements and the environmental advantages of drone deliveries. The research also addresses critical aspects such as autonomy, navigation, obstacle avoidance, traffic control and the essential sensors needed for efficient drone operations. By looking into possibilities in quick response delivery systems and delivery time reductions, the thesis explores the potentials of drone deliveries and automated logistics. Despite regulatory and technical limitations, the thesis lays the groundwork for future delivery systems. While acknowledging the lack in regulations, infrastructure, demand, and lack of financing incentives and technology, the thesis concludes that the adoption of drone delivery systems is still something to invest in. This technology opens new greener possibilities in societal infrastructure, such as flexibility, efficiency, and environmental benefits and paves the way for a new era of lifestyle improvements.

Kandidaatintutkielma 'Exploring the application and integration of UAV technology in delivery systems' käsittelee autonomisten UAV-lennokkien maailmaa ja miten tällaista teknologiaa voidaan integroida kuljetusjärjestelmiin. Tutkimus alkaa selittämällä perusteellisesti miten erilaiset lentokonerungot toimivat, sekä kertomalla niiden vahvuudet ja heikkoudet. Laskeutumistelakka yhdistää sekä FMS (joustavat valmistusjärjestelmät) -teknologian että automatisoinnin. Käyttäen telakkaa lennokit muodostavat erittäin kilpailukykyisen ja hyödyllisen vaihtoehdon autopohjaisille toimitusjärjestelmille. Drone-pohjaisilla toimitusjärjestelmillä on pienempi hiilijalanjälki toimituskilometriä kohti, ja ne ovat nopeampia ja joustavampia verrattuna fossiilisia polttoaineita kuluttaviin autotoimitusmenetelmiin. Induktiivisen rakenteen avulla tutkielma käsittelee aerodynamiikkaa, anturivaatimuksia ja hypoteettista toimitusjärjestelmää Turun kaupungissa Suomessa. Tässä tutkimuksessa tutkielma päättelee, mitkä sektorit hyötyisivät tällaisista toimitusjärjestelmistä haastattelemalla henkilöstöä näistä sektoreista. Analyysi laajenee infrastruktuurivaatimusten ja drone-toimitusten ympäristöetujen huomioimiseen. Tutkimus käsittelee myös kriittisiä näkökohtia, kuten autonomiaa, navigointia, esteiden väistämistä, liikenteenohjausta ja tehokkaiden drone-toimintojen kannalta välttämättömiä antureita. Tutkielma käsittelee drone-toimitusten ja automatisoidun logistiikan potentiaalia tarkastelemalla nopeita reagointitoimitusjärjestelmiä ja toimitusaikojen lyhentämisen mahdollisuuksia. huolimatta tämän hetken sääntely- ja teknisistä rajoituksista, tutkielma luo pohjan tulevaisuuden toimitusjärjestelmille. Ottaen huomioon lakisääntely, infrastruktuurin, kysynnän, rahoitus- ja teknologiapohjaisten kannustimien puutteen, tutkielma päättelee, että drone-toimitusjärjestelmiin sijoittaminen on kannattavaa. Tämä teknologia avaa uusia vihreitä mahdollisuuksia yhteiskunnalliselle infrastruktuurille, kuten joustavuudelle, tehokkuudelle ja ympäristöeduille, ja avaa tien uudelle elämänlaadun parantamisen aikakaudelle.
Keywords: UAV, Drone, Delivery system, Aerodynamics, Fixed-wing aircraft, Rotary-wing aircraft